Allometric Models of Rhizophora apiculata Biomass in Polewali Mandar District, West Sulawesi Province - Ruslianto Ruslianto (Balai Penelitian dan Pengembangan Lingkungan Hidup dan Kehutanan Makassar, 2019)
Mangrove forests take an essential role in mitigating climate change, through its ability of photosynthetic and storing carbon. Information on biomass and carbon potentially stored in mangrove forests is very important for presenting allometric models as a reference for estimating plants biomass. To date, there have been 15 allometric models for Rhizophora sp., but allometric models for estimating Rhizophora sp. biomass in Polewali Mandar regency remain unidentified. Rhizophora apiculata in Polewali Mandar District is widespread species, almost found in all mangrove forest areas. The research was carried out through 4 stages, which were selection of 10 tree samples, measurement of fresh weight, measurement of moisture content, and measurement of dry weight (biomass). Substitution of measurement values in allometric equations, and analysis of data used the scoring method coefficient of determination variable (R2), bias, error-index, and Mean Square Error Prediction. The study found that the best allometric model with the highest scoring value was Ŷ = 1.02D0,949H1,142.